Lobachevski illuminated - Braver, Seth (MAA spectrum., 2011)
Lobachevski Illuminated provides an historical introduction to non-Euclidean geometry. Within its pages, readers will be guided step-by-step through a new translation of Lobachevski's groundbreaking book, The Theory of Parallels. Extensive commentary situates Lobachevski work in its mathematical, historical, and philosophical context, thus granting readers a vision of the mysterious and beautiful world of non-Euclidean geometry as seen through the eyes of one of its discoverers. Although Lobachevski 170-year old text is challenging to read on its own, Seth Braver, carefully arranged 'illuminations' render this classic accessible to any modern reader (student, professional, or layman) undaunted by high school mathematics.